Factors Related with Hypertension; A Cross Sectional Study at Puskesmas Kota Selatan, Puskesmas Kota Timur, Puskesmas Kota Utara, Gorontalo City - Miftahunnisa Danti Ilato; Ida Leida Maria; Rismayanti (Universitas Widya Gama Mahakam Samarinda, 2024)
Background: Hypertension is a global health problem characterized by an increase in systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg in two measurements with an interval of five minutes and in a state of sufficient rest. Objectives: To determine the factors associated with the incidence of hypertension at Puskesmas Kota Selatan, Puskesmas Kota Timur, and Puskesmas Kota Utara. Research Metodes: This type of research is analytic observational using a cross-sectional study . The population in this study was 3,542 people, with a sample of 230 people. The sampling technique uses proportional random sampling. Data were analyzed univariate and bivariate using the chi-square test. Results: This study showed that out of a total of 230 respondents, there were 105 respondents with hypertension and125 people with normal blood pressure. Age (p=0.000), family history of hypertension (p=0.000), smoking status (p=0.000), physical activity (p=0.000), obesity status (p=0.000), and stress status (p=0.000) had a relationship with the incidence of hypertension. Gender (p=0.754) and coffee consumption (p=0.761) showed no association with the incidence of hypertension. Conclusion: Age, family history of hypertension, smoking status, physical activity, obesity, and stress status are related to the incidence of hypertension. The community should adopt a healthy lifestyle as an effort to improve health status, significantly reduce the incidence of hypertension Keywords: hypertension; factors; Gorontalo City